2014
DOI: 10.2147/ppa.s54986
|View full text |Cite
|
Sign up to set email alerts
|

An observational, retrospective, UK and Ireland audit of patient adherence to subcutaneous interferon beta-1a injections using the RebiSmart® injection device

Abstract: BackgroundPoor adherence to disease-modifying drugs is associated with an increased risk of relapse in patients with multiple sclerosis. However, adherence is difficult to assess objectively. RebiSmart® (Merck Serono SA, Geneva, Switzerland), a device for subcutaneous (sc) injection of interferon (IFN) β-1a, features an electronic injection log that can assist in objective monitoring of adherence.ObjectiveTo assess adherence to sc IFN β-1a injections using data from RebiSmart®.MethodsThis was a single-group, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In contrast to our study, these studies were based on medical and pharmacy claims data, and adherent patients were defined as showing a medication possession ratio (MPR) ≥0.8 at observation periods of 12–36 months22 or 24 months,4 respectively. The MPR is a common method for measuring adherence based on dispensed medication, but it cannot verify that the medication has actually been used, and it may be prone to overestimation of adherence 17. In addition, the data analyzed in these studies4,22 originate from a time (between 2000 and 2009) when the IFN beta-Ia autoinjector device had not yet been available for the administration of sc IFN beta-1a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to our study, these studies were based on medical and pharmacy claims data, and adherent patients were defined as showing a medication possession ratio (MPR) ≥0.8 at observation periods of 12–36 months22 or 24 months,4 respectively. The MPR is a common method for measuring adherence based on dispensed medication, but it cannot verify that the medication has actually been used, and it may be prone to overestimation of adherence 17. In addition, the data analyzed in these studies4,22 originate from a time (between 2000 and 2009) when the IFN beta-Ia autoinjector device had not yet been available for the administration of sc IFN beta-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Although slightly lower, the adherence rates observed in our study are in line with those seen in these three studies. The retrospective analysis by Willis et al17 of the IFN beta-Ia autoinjector device data from 225 patients in the UK and Ireland, who continued therapy for at least 2 years, yielded a mean adherence rate of 95% and showed that 91% of the patients were adherent (≥80% adherence) at month 24. A prospective observational study in 119 patients in Italy showed that after 12 weeks of treatment, 88% of the patients were adherent (≥80% adherence) 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of smaller uncontrolled trials with follow-up periods between 12 weeks and 1.5 years revealed high adherence of ≥80%-90%. [21][22][23][24][25][26][27] Lugaresi et al 28,29 found a decrease in adherence (among completers) from 100% through week 4 to 99.1% in weeks 5-8, to 89.0% in weeks 9-12. After a long-term follow-up of 20.5 months, overall adherence was further decreased to 79.8%.…”
Section: Rebismart ®mentioning
confidence: 98%
“…Adherence to injectable DMTs and other interventional strategies is usually considered inferior in MS patients [10][11][12][13][14][15][16]; a retrospective study of MS patients initiating therapy with 1 of 4 injectable DMTs found that after 18 months, 11.2% of patients switched their medication, and 33.9% discontinued their treatment [17]. An adherence study on ambulatory patients carried out in Spain showed that after 2 years of starting DMT, INF-β was discontinued in 9.9% of patients, after 5 years discontinuation rose to 41.2% and after 8 years discontinuation rate was 58.7% [18].…”
Section: Plos Onementioning
confidence: 99%